Firm characteristics and tax aggressiveness of quoted companies in Nigeria - Martins, Otuedon Ajueyitse; Sule, Omoye Alade (The Economics and Finance Letters, 2024)
This study examined the firm characteristics of tax aggressiveness among quoted companies in Nigeria. The specific objectives were to determine the influence of firm size, profitability, liquidity and leverage on the tax aggressiveness of firms. It was an ex-post-facto and longitudinal study that spanned five years (2015-2019). The population consisted of 87 non-financial companies while the sample size was 67. The data used were from the financial statements and accounts of the sampled companies. The statistical techniques used include descriptive statistics, correlations and random and fixed effects panel least squares regression. The study showed that firm size and profitability have a significant influence and positive relationship with tax aggressiveness while liquidity has no significant influence on tax aggressiveness but has a positive relationship with it. Leverage had a significant influence while having a negative relationship with tax aggressiveness. It was concluded that firm characteristics are critical factors influencing tax aggressiveness among quoted companies in Nigeria. It recommended that a company’s size should not be the basis for tax aggressiveness and that its profitability, liquidity and leverage position be disclosed in a way that accurately reflects its financial status. It will be of immense benefit to companies to ensure that their tax strategies align with ethical and legal standards and that they maintain transparency in their financial reporting. Similarly, the findings of this study have important implications for government tax authorities at both the federal and state levels in terms of the assessment of companies for tax purposes.